Boosting High‐Rate Sodium Storage Performance of N‐Doped Carbon‐Encapsulated Na3V2(PO4)3 Nanoparticles Anchoring on Carbon Cloth. Issue 43 (6th September 2019) - Li, Wei; Yao, Zhujun; Zhou, Cheng‐ao; Wang, Xiuli; Xia, Xinhui; Gu, Changdong; Tu, Jiangping
Abstract: The further development of high‐power sodium‐ion batteries faces the severe challenge of achieving high‐rate cathode materials. Here, an integrated flexible electrode is constructed by smart combination of a conductive carbon cloth fiber skeleton and N‐doped carbon (NC) shell on Na3 V2 (PO4 )3 (NVP) nanoparticles via a simple impregnation method. In addition to the great electronic conductivity and high flexibility of carbon cloth, the NC shell also promotes ion/electron transport in the electrode. The flexible NVP@NC electrode renders preeminent rate capacities (80.7 mAh g −1 at 50 C for cathode; 48 mAh g −1 at 30 C for anode) and superior cycle performance. A flexible symmetric NVP@NC//NVP@NC full cell is endowed with fairly excellent rate performance as well as good cycle stability. The results demonstrate a powerful polybasic strategy design for fabricating electrodes with optimal performance. Abstract : An integrated NVP@NC flexible electrode is constructed by smart combination of a conductive carbon cloth skeleton and N‐doped carbon shell on Na3 V2 (PO4 )3 nanoparticles with superior Na storage performances.